Lead-Free Perovskite Materials for Solar Cells - Wang, Minghao; Wang, Wei; Ma, Ben; Shen, Wei; Liu, Lihui; Cao, Kun; Chen, Shufen; Huang, Wei (Nano-Micro Letters, 2021)
The toxicity issue of lead hinders large-scale commercial production and photovoltaic field application of lead halide perovskites. Some novel non- or low-toxic perovskite materials have been explored for development of environmentally friendly lead-free perovskite solar cells (PSCs). This review studies the substitution of equivalent/heterovalent metals for Pb based on first-principles calculation, summarizes the theoretical basis of lead-free perovskites, and screens out some promising lead-free candidates with suitable bandgap, optical, and electrical properties. Then, it reports notable achievements for the experimental studies of lead-free perovskites to date, including the crystal structure and material bandgap for all of lead-free materials and photovoltaic performance and stability for corresponding devices. The review finally discusses challenges facing the successful development and commercialization of lead-free PSCs and predicts the prospect of lead-free PSCs in the future. Highlights: 1 The toxicity issue of lead-based halide perovskites hinders theirs large-scale commercial applications in solar cells. 2 A variety of non- or low-toxic perovskite materials have been used for development of environmentally friendly lead-free perovskite solar cells, some of which show excellent optoelectronic properties and device performances. 3 At present, more new lead-free perovskite materials with tunable optical and electrical properties are urgently required to design highly efficient and stable lead-free perovskite solar cells.